2014
DOI: 10.1177/0269215514527597
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of the Nintendo Wii™ for balance training post-stroke: a phase II randomized controlled trial in an inpatient setting

Abstract: A Wii-based approach appears feasible and promising for post-stroke balance rehabilitation. A larger randomized controlled trial is recommended to further investigate efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 31 publications
7
55
2
5
Order By: Relevance
“…Contrary to our findings, an RCT showed that improvements in functional balance were significantly higher in Wii group [22]. Also Wii Fit training proved to be more effective than usual balance therapy in improving functional balance (Berg Balance Schale) and independence in activity of daily living (Barthel index) [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, an RCT showed that improvements in functional balance were significantly higher in Wii group [22]. Also Wii Fit training proved to be more effective than usual balance therapy in improving functional balance (Berg Balance Schale) and independence in activity of daily living (Barthel index) [19].…”
Section: Discussioncontrasting
confidence: 99%
“…The Nintendo Wii is safe and has no side effects. Moreover, it has the benefit of producing higher motivation in clients because they are playing a game and receive immediate feedback from the screen (Bower, Clark, Mcginley, Martin, & Miller, 2014;Keogh, Justin, W., et al, 2014). Keog et al (2014) described the positive effect of the Wii on functional ability and improvements in upper limb strength in elderly subjects after eight weeks of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Keog et al (2014) described the positive effect of the Wii on functional ability and improvements in upper limb strength in elderly subjects after eight weeks of intervention. Additionally, a study on patients recovering from stroke (Bower, et al, 2014) showed a positive effect on upper limb strength development after only two to four weeks of intervention. Toulotte, Toursel and Olivier (2012) showed that twenty weeks of Nintendo Wii balance training in a healthy elderly population improved results of clinical tests (Tinetti and Unipedal tests) and also improved stability during a Wii fit test, which was measured as the centre of pressure (COP) movement and distribution of pressure between the right and left foot -calculated as the difference between the percentage of position of the COP on each foot.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic options for weight shift and balance training have recently been expanded with the growth in popularity of virtual gaming systems [1][2][3][4]. One such device that integrates virtual gaming with body movement is the Nintendo Wii, a popular gaming console that allows the player to interact with the game via three-dimensional movements [1,5]. This study examined the feasibility and safety of using the Wii Fit as an adjunct to outpatient physiotherapy following lower limb fractures, and reports sample size considerations for an appropriately powered randomised trial.…”
mentioning
confidence: 99%